Effect of neighbourhood economic characteristics on the health of individuals - O'Grady, Kathryn (University of Ottawa (Canada), 2005)
This multilevel study examined the influence of neighbourhood socioeconomic context on individual health as measured by self-rated health status and the Health Utilities Index (HUI) in urban neighbourhoods of the City of Ottawa and the combined cities of Ottawa and Gatineau. The samples were drawn from the respondents to the Canadian Community Health Survey 2000--2001 which included individuals 12 years of age and older. There were 1441 respondents within the 37 Ottawa neighbourhoods and 711 respondents within the 14 Gatineau neighbourhoods. The neighbourhood characteristics were derived from the 2001 Census. In Ottawa there was significant variation in health at the neighbourhood level. In age-adjusted models the neighbourhood low income rate and the neighbourhood low education rate were significantly associated with self-rated health (OR=1.35, 95% CI 1.01--1.81; OR=1.03, 95% CI 1.00--1.06, respectively) and a HUI score <0.973 (OR=1.31, 95% CI 1.10--1.56; OR=1.27, 95% CI 1.07--1.52, respectively). However, adjustment for individual level factors reduced the influence of the neighbourhood level variables such that they were no longer statistically significant. Similar results were found for the analysis of the combined cities. This study suggests that the differences in health between neighbourhoods of Ottawa and Ottawa-Gatineau can be attributed primarily to the compositional impact of the characteristics of individuals within the neighbourhoods.
Keywords: Health Sciences, Public Health.